2001
DOI: 10.1111/j.1471-0528.2001.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of interleukin-10 and transforming growth factor-beta in the plasma and ascitic fluid of patients with advanced ovarian cancer

Abstract: aObjectives To assess expression of the immunosuppressive cytokines IL-10 and TGF-b in the ascitic¯uid and plasma of advanced ovarian cancer patients. Design A prospective study.Setting The Department of Obstetrics and Gynaecology at the University of Arkansas for Medical Sciences.Population Twenty-eight women diagnosed with advanced ovarian cancer and ten normal female controls. Methods Plasma and ascitic samples were collected at the time of surgery and analysed for the presence of IL-10 and TGF-b using a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…Furthermore, TGF-β1 stimulates matrix metalloproteinase secretion, thereby promoting OC cell invasion [39]. Several clinical studies report that TGF-β1 and TGF-β1-binding protein mRNAs are elevated in OC tissue and in ascites fluid [19,40]. Although melatonin has been shown to activate the TGF-β1 pathway related to growth inhibition of breast cancer cells [41], we observed an antagonizing effect of melatonin on TGF-β1 and VEGF levels in the course of OC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TGF-β1 stimulates matrix metalloproteinase secretion, thereby promoting OC cell invasion [39]. Several clinical studies report that TGF-β1 and TGF-β1-binding protein mRNAs are elevated in OC tissue and in ascites fluid [19,40]. Although melatonin has been shown to activate the TGF-β1 pathway related to growth inhibition of breast cancer cells [41], we observed an antagonizing effect of melatonin on TGF-β1 and VEGF levels in the course of OC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the immunosuppressive cytokine TGF-β, which is regularly detected in ovarian and cervical cancer (45)(46)(47), seems to induce this inhibiting receptor on T cells (44). Several studies have shown that the inhibiting receptor CD94/NKG2A dampens the incoming activation signals of T cells by recruitment of phosphatases like SHP-1 to the signal transducing synaps, resulting in decreased effector functions (1,44,48).…”
Section: Discussionmentioning
confidence: 99%
“…Santinet et al (Santin et al, 2001) found a higher expression levels of TGF-β among PBMCs in oophoroma patients. This was similar with the result made in our paper.…”
Section: Discussionmentioning
confidence: 99%